Legal Aspects of Computerization in Accounting - Osikowicz , Marcin (Studia Oeconomica Posnaniensia, 2018)
Computerization is an inevitable process in accounting. On the one hand it is determined with the internal needs of entities. On the other it is determined with the legal environment especially tax law and accounting law. The main aim of this article was to find a set of legal norms which has the most significant influence on the informatisation process in accounting. Following a detailed analysis of the key provisions, it is important to note that the Accounting Act determines many functionalities of accounting programs. Currently the Tax Code and its norms have concerned the Single Tax Files which play the most significant role.